2019
DOI: 10.1088/1361-6560/ab325c
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Compton radiation: a novel x-ray source for K-edge subtraction angiography?

Abstract: Coronary angiography is clinically used worldwide to diagnose diseases of coronary arteries. Despite its effectiveness, this technique is quite invasive and it is associated to significant risks due to the arterial catheterisation needed to inject the contrast agent. A valid alternative is using the K-edge subtraction method, which is based on the subtraction of two images acquired at energies bracketing the K-edge of the contrast element. The enhanced sensitivity of K-edge subtraction allows the intravenous i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…A fluence of about 1 ×10 7 ph mm −2 is barely sufficient to image the smallest vessels considered here (2.5 mm diameter) with a contrast medium concentration of 10 mg mL −1 . Higher values of fluence guarantee a better visibility of the smaller details with less contrast medium, as estimated in our previous work [54]. Our results are also compatible with past studies aimed at investigating the effects of energy separation [61] and energy spread [53] in KES imaging.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A fluence of about 1 ×10 7 ph mm −2 is barely sufficient to image the smallest vessels considered here (2.5 mm diameter) with a contrast medium concentration of 10 mg mL −1 . Higher values of fluence guarantee a better visibility of the smaller details with less contrast medium, as estimated in our previous work [54]. Our results are also compatible with past studies aimed at investigating the effects of energy separation [61] and energy spread [53] in KES imaging.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, the signal of the bone competes with the signal of the small blood vessels perfused with the contrast medium. Furthermore, coronary angiography is much more demanding in terms of X-ray beam intensities, due to the significant attenuation of surrounding tissues in the chest [54]. A careful setting of the ICS X-ray beams is mandatory to obtain a correct reconstruction of the mass thickness of the iodinated structures, a sufficient SNR in the contrast image and a good rejection of the bone signal (coronary angiography).…”
Section: Resultsmentioning
confidence: 99%
“…In a simulation study, Paterno et al [67] evaluated the applicability of KES at ICSs for a realistic dilution of the iodine contrast agent in arteries and the projected beam parameters of the proposed BriXS project [28]. They found that ICSs have to deliver a fluence of 10 8 ph/mm 2 at the sample plane to image most arteries with sufficient contrast and acquisition times of a few hundred milliseconds, which is significantly higher than demonstrated up to now.…”
Section: Future Developmentsmentioning
confidence: 99%
“…X-ray imaging tests with ICS sources using contrast agents have been reported with (quasi-)monochromatic beam at a single energy above the K-edge of iodine [16,17], as well as using filtration of the same material used as contrast medium and specific reconstruction algorithms [18,19]. Also, simulations of the application of KES technique with X-ray beams of proposed ICS facilities demonstrated the potential of these sources in the case of coronary angiography and contrast-enhanced dual-energy mammography [20,21]. Nonetheless, dualenergy KES experiments with ICS have never been carried out so far, due to the lack of an effective implemen-tation of a fast dual-energy switch.…”
Section: Introductionmentioning
confidence: 99%